Exploring brain development as a mediator for adverse childhood experiences and resilience - Tan, Ivan Jia Le (Nanyang Technological University, 2024)
Adverse childhood experiences (ACEs) refer to negative experiences between 0 – 18 years old. This period is developmentally sensitive to environmental influences and ACEs increase the risk of somatic and psychological dysfunction across the lifespan. High global prevalence makes research into its neurobiological mechanisms paramount. Outcome resilience refers to adaptive functioning post-ACEs, inferred by the ability to function within everyday environments. This study inferred outcome resilience from adaptive functioning in educational, social settings, and neurocognitive domains. Past literature found the hippocampus, amygdala, and pre-frontal cortex were associated with ACEs-resilience. However, studies establishing a causal relationship between ACEs-brain-resilience are limited. Hence, this study aims to determine if these brain regions mediate ACEs-resilience. The Adolescent Brain Cognitive Development Study (ABCD) is an ongoing longitudinal study involving 11,878 participants. Gray matter volumes and volume changes from 2016 – 2021 were used for mediation analysis. There is no evidence to support that these brain regions mediate the relationship between ACEs-resilience. However, across the three resilience domains, different brain structures had significant associations with minimal overlaps. This suggests that the domains do not redundantly measure the same constructs. Future research should not treat resilience as a catch-all unitary construct, measuring various domains of adaptive functioning.